PENINGKATAN KETERAMPILAN MENULIS TEKS EKSPLANASI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN COOPERATIVE, INTEGRATED, READING AND COMPOSITION (CIRC) SISWA KELAS VII.1 MTS. MUHAMMADIYAH TALLO KOTA MAKASSAR - Ira Afrianti; M. Agus; Wahyu Ningsih (STKIP Subang, 2025)
This study aims to improve the writing skills of explanatory texts of class VII.1students at MTs. Muhammadiyah Tallo, Makassar City, through the application ofthe Cooperative, Integrated, Reading, and Composition (CIRC) learning model.This study focuses on the main question: